The Effectiveness Comparison Between Application of Indigenous Arbuscular Mycorrhizal Fungal Community and Stenotrophomonas maltophilia to Suppress Fusarium Wilt Incidence on Local Garlic Plant (Lumbu Hijau) - Rifani Rusiana Dewi; Syarifah Maulidya Rahmah; Ardiyan Taruna; Luqman Qurata Aini; Ito Fernando; Abdul Latief Abadi; Muhammad Akhid Syib’li (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
Wilt disease caused by Fusarium oxysporum is one of the most serious plant diseases in the world. There is no effective contol for. This study investigated the potential of arbuscular mycorrhizal and bacterial antagonists to control F. oxysporum through in vitro and in vivo studies. In this study, the antagonistic bacteria Stenotrophomonas maltophilia was isolated from mycorrhizal propagation media. Antagonist bacteria S. maltophilia showed antagonistic ability against F. oxysporum with an inhibition zone of 17.9 cm. Antagonistic bacteria and mycorrhizae used in this study significantly reduced the incidence of fusarium wilt in in vivo experiments. It was found that mycorrhizal and S. maltophilia inoculation showed disease incidence rates at 40% and 47.6%. While in the control treatment the incidence of disease reached 90.3%. The biocontrol agents of S. maltophilia and mycorrhizae have a promising prospective strategy to protect garlic plants. These results are expected to provide new insights for sustainable crop protection systems.